2021
DOI: 10.1111/nph.17398
|View full text |Cite
|
Sign up to set email alerts
|

Callose accumulation in specific phloem cell types reduces axillary bud growth in Arabidopsis thaliana

Abstract: Callose accumulation in specific phloem cell types reduces axillary bud growth in Arabidopsis thaliana

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…This signal has been assigned to sucrose and trehalose-6-phosphate (T6P), whose levels increase rapidly after decapitation (Fichtner et al, 2017(Fichtner et al, , 2021Barbier et al, 2019). In agreement with such a scenario, elegant recent work with cell-specific genetic manipulation of phloem transport (Paterlini et al, 2021) and sugar supply (Fichtner et al, 2021) indicated that sugars may indeed contribute to axillary bud activation in Arabidopsis. Since BRC1 expression is repressed by sugars (Mason et al, 2014;Barbier et al, 2015;Otori et al, 2019;Patil et al, 2022), a plausible model is that sugars contribute to bud outgrowth by attenuating BRC1-dependent dormancy (Wang et al, 2019).…”
Section: How Are Buds Triggered To Grow Out When They Are Released Fr...mentioning
confidence: 82%
See 2 more Smart Citations
“…This signal has been assigned to sucrose and trehalose-6-phosphate (T6P), whose levels increase rapidly after decapitation (Fichtner et al, 2017(Fichtner et al, , 2021Barbier et al, 2019). In agreement with such a scenario, elegant recent work with cell-specific genetic manipulation of phloem transport (Paterlini et al, 2021) and sugar supply (Fichtner et al, 2021) indicated that sugars may indeed contribute to axillary bud activation in Arabidopsis. Since BRC1 expression is repressed by sugars (Mason et al, 2014;Barbier et al, 2015;Otori et al, 2019;Patil et al, 2022), a plausible model is that sugars contribute to bud outgrowth by attenuating BRC1-dependent dormancy (Wang et al, 2019).…”
Section: How Are Buds Triggered To Grow Out When They Are Released Fr...mentioning
confidence: 82%
“…Hence, decapitation could potentially lead to bushy shoot phenotypes as in mutants with decreased AD ( max , dad , rms, and dwarf ). However, this is normally not the case, because the remaining buds are in mutual competition ( Crawford et al, 2010 ; Shinohara et al, 2013 ; Balla et al, 2016 ; Paterlini et al, 2021 ), and often, one bud rapidly outcompetes all the others. Therefore, soon after decapitation, AD is reestablished resulting in a single new main shoot.…”
Section: Competition Among Buds Kicks In Via Auxin...mentioning
confidence: 99%
See 1 more Smart Citation
“…In perennial plants, bud dormancy is induced in response to short days by callose deposition in plasmodesmata, which restricts symplastic cellcell signaling and metabolite flux in the shoot apical meristem (van der Schoot & Rinne, 2011). In a recent study, Paterlini et al (2021) investigated if an increase in callose synthesis would inhibit axillary bud outgrowth in Arabidopsis. Using the iclas3 system, the authors increased callose biosynthesis in Arabidopsis companion cells and phloem parenchyma cells, and investigated the effect on axillary bud growth in intact and decapitated excised inflorescence stem sections containing one or two axillary buds.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In perennial plants, bud dormancy is induced in response to short days by callose deposition in plasmodesmata, which restricts symplastic cell-cell signaling and metabolite flux in the shoot apical meristem ( van der Schoot & Rinne, 2011 ). In a recent study, Paterlini et al. (2021) investigated if an increase in callose synthesis would inhibit axillary bud outgrowth in Arabidopsis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%